Illustrissimi philosophi & theologi, domini Alberti magni co[m]pendiosum, isigne, ac perutile opus Philosophie naturalis - Albertus, of Orlamünde, Dominican (Incunabula. Printing in Venice.)
This work, commonly known as the Philosophia pauperum, is now generally ascribed to Albertus of Orlamünde, not Albertus Magnus. It primarily contains extracts from Albertus Magnus, including version "B" of De anima, and the first and third books of Giles of Rome's De regimine principum and his De passionibus anime. Cf. B. Geyer in Albertus, of Orlamünde. Die Albert dem Grossen zugeschriebene Summa naturalium (Philosophia pauperum) Münster, 1938, p. 60-62.